Building Characters and Socio-Culture Values to Generation Z of Batik Craftsman Family in Pekalongan - Mayangsari, Cintya Anindita; Utomo, Cahyo Budi; Pujiati, Amin (Universitas Negeri Semarang, 2020)
The use of internet technology allows parents and children activities to be higher and more diverse. From the family aspect, this condition allows changes in the parents’ roles in educating their children. Furthermore, when it is viewed from the children aspect, it is possible to change the meaning of social values ​​by the generation Z. Based on this phenomenon, there are two important issues that need to be studied. First, this research aims to reveal the parents’ roles in building characters of socio-cultural values ​​to Generation Z. Second, it aims to reveal the meaning of socio-cultural values ​​by Generation Z. The research used a qualitative approach with the Habitus theory initiated by Bourdieu as the data analysis technique. The research findings showed that the parents’ roles in building socio-cultural character can be divided into two categories. The first category is families that always provide parental accompaniment to their children and the second category is families that barely provide parental accompaniment to their children. Furthermore, based on the meaning of socio-cultural values, the social interaction value was interpreted as a communication with other people that does not have social implications. The other interpreted social interaction as a communication between two or more people with social implications. The value of solidarity was interpreted as a form of concern for others, while lifestyle was interpreted as a form of appearance that has no social implications and others considered it to have social implications. The value of tolerance was interpreted as the behavior of respecting differences.